Factors affecting consumers behavioral intention to share digital footprints on social media - Leong, Jenny Siew Yee (2024)
The emergence of social media has streamlined the transmission of information through various avenues, prompting individuals to supplant traditional methods with the integration of social platforms. In this era of state-of-the-art technology and the prevalence of big data in media channels, numerous touchpoints that consumers encounter on their technological devices at any time and place result in the creation of digital footprints, which companies can analyze to tailor advertisements and ultimately enhance sales.